Basic procedure for the in vitro propagation of Brazilian trees for reforestation purposes - Souza, Robson Antonio de; Dantas, Patricia Virgínia Palhares; Cavalcante, Paloma de Freitas; Tenório, Ramon Rocha; Houllou, Laureen Michelle (Journal of Environmental Analysis and Progress, 2017)
Important strategies can be used to avoid biodiversity loss by deforestation in tropical rainforests. Some use biotechnological techniques to support conservation initiatives. Plant tissue culture techniques are highly accepted biotechnological approaches for conservation of biodiversity. The work aimed to propose a basic operational model for the induction of in vitro germination of trees through plant tissue cultivation techniques. Fruits of 15 tree species, ten woody trees (Couroupita guianensis Aubl., Tabebuia heptaphylla (Vell.) Toledo, Tabebuia impetiginosa (Mart. ex DC.) Standl., Tabebuia roseoalba (Ridl.) Sandwith, Vochysia haenkeana (Spreng.) Mart., Vitex montevidensis Cham., Copaifera coriacea Mart., Spondias tuberosa Arruda, Schinus terebinthifolia Raddi, and Talisia esculenta (A. St.-Hil.) Radlk.) and five palm trees (Syagrus coronate (Mart.) Becc., Attalea oleifera Barb. Rodr., Elaeis guineensis Jacq., Colubrina glandulosa Perk., and Astrocaryum vulgare Mart.) were collected at different locations in the State of Pernambuco, Brazil. The in vitro germination used two different protocols, one designed for palm trees and one designed for woody trees. It was evaluated the parameters microbial contamination, survival, in vitro establishment, germination percentage and percentage of seeds converted to plants. The results showed that the set of methodologies proposed as a basic protocol for the in vitro introduction was able to achieve satisfactory results for 13 of the 15 tested species. The protocol proposed a high potential for use in the rescue of seeds through in vitro plant tissue culture. The described technique is an efficient tool for the propagation of trees used in reforestation programs.